Traumatic Spinal Cord Injury Alters Angiogenic Factors and TGF-Beta1 that may Affect Vascular Recovery - Ritz, Marie-Francoise; Graumann, Ursula; Gutierrez, Bertha; Hausmann, Oliver; E (Current Neurovascular Research, 2010)
Traumatic spinal cord injury (SCI) disrupts the blood-spinal cord barrier and reduces the blood supply caused by microvascular changes. Vessel regression and neovascularization have been observed in the course of secondary injury contributing to microvascular remodeling after trauma. Spatio-temporal distribution of blood vessels and modulation of gene expression of several angiogenic factors have been investigated in rats after spinal cord compression injury. after 2 and 4 weeks, whereas no changes were observed in the penumbra. Investigation of the temporal expression of angiogenic genes using quantitative RT-PCR disclosed a constant down-regulation of the vascular endothelial growth factor (VEGF), and transient decreases of angiopoietin-1 (Ang-1), platelet-derived growth factor-BB (PDGF-BB), as well as placental growth factor (PlGF), with the lowest values obtained 3 days after injury, when compared to the expression levels obtained in sham-operated rats. Hepatocyte growth factor (HGF) was the only angiogenic factor with a constant increased gene expression when compared with controls, starting at day 3 post-SCI. mRNA levels of transforming growth factor-beta 1 (TGF-β1) were elevated at every time point following SCI, whereas those encoding for the cysteine-rich protein CCN1/CYR61 were upregulated after 2 h, 6 h, and 1 week only. Our data provide an overview of the temporal modulated expression of the major angiogenic factors, hampering revascularization in the lesion during the phase of secondary injury. These findings should be considered in order to improve therapeutic interventions.
Keywords: TGF-Beta1